The Effect of Coping Strategies, Psychological Distress, and Psychological Flexibility on Pain Catastrophizing with the Mediating Role of Emotion Regulation - Fathi , Azin; Arab, Simin; Ebrahimirad , Reza (Mental Health and Lifestyle Journal, 2025)
This study aimed to investigate the predictive role of coping strategies, psychological distress, and psychological flexibility on pain catastrophizing, while examining the mediating role of emotion regulation in patients with migraine. In a descriptive-analytical design, 200 migraine patients (124 women, 62%; 76 men, 38%; mean age = 35.5 years, SD = 8.12) were recruited from two specialized pain clinics in Tehran between September and December 2024. Participants completed validated questionnaires, including the Pain Catastrophizing Scale (PCS), Coping Strategies Questionnaire (CSQ), Kessler Psychological Distress Scale (K10), Persian Psychological Flexibility Index (P-PPFI), and Emotion Regulation Questionnaire (ERQ). Data were analyzed using SmartPLS 4.0.9, with assessment of measurement reliability and validity, and structural equation modeling tested with bootstrapping (5,000 resamples). Psychological distress directly predicted higher pain catastrophizing (β = .41, p < .001), while psychological flexibility reduced catastrophizing both directly (β = –.29, p < .001) and indirectly via emotion regulation (β = –.14, p = .001). Coping strategies showed differential effects: distraction (β = –.17, p = .008) and reappraisal (β = –.19, p = .004) reduced catastrophizing, whereas attention to pain increased it (β = .22, p = .002). Among emotion regulation strategies, cognitive reappraisal predicted lower catastrophizing (β = –.23, p = .001), whereas expressive suppression predicted higher catastrophizing (β = .18, p = .009). Model fit indices confirmed adequacy (χ²/df = 1.37; CFI = .95; RMSEA = .041). Findings suggest that psychological distress is a primary risk factor for pain catastrophizing in migraine patients, whereas psychological flexibility and adaptive coping serve protective functions through emotion regulation. Integrative interventions targeting distress, flexibility, and regulation strategies may reduce catastrophizing and improve clinical outcomes.